Democratising or Demonising the World Heritage Convention? - Affolder, Natasha (Victoria University of Wellington Law Review, 2007)
In recent disputes surrounding mining projects in and around World Heritage sites, the legitimacy of the World Heritage Convention regime has been attacked for a host of democratic failings. These accusations of ’democratic deficits’ originate from both opponents and supporters of the Convention regime. They challenge the compatibility of international processes with national law and institutions, raise questions of accountability and transparency, and revisit tensions between state sovereignty and common heritage. This paper traces these perceptions of democratic shortcomings in the regime to certain misunderstandings of the Convention, to failed participatory processes at the national level, and to the challenges posed by vague and illdefined treaty obligations. At the same time as it unveils democratic concerns about the evolving nature of the treaty regime, this paper challenges us to consider the democratic strengths of the Convention.